Walt Whitman's Selected Journalism - Whitman, Walt, 1819-1892 (Book collections on Project MUSE., 2014)
Long before he was a celebrated poet, Walt Whitman was a working journalist. By the time he published the first edition of Leaves of Grass in 1855, Whitman had edited three newspapers and published thousands of reviews, editorials, and human-interest stories in newspapers in and around New York City. Yet for decades, much of his journalism has been difficult to access or even find. For the first time, Walt Whitman's Selected Journalism thematically and chronologically organizes a compelling selection of Whitman's journalism from the late 1830s to the Civil War. It includes writings from the po.